Effect of CaCO3-saturated solution on CO2 corrosion of mild steel explored in a system with controlled water chemistry and well-defined mass transfer conditions. (September 2019) - Mansoori, H.; Young, D.; Brown, B.; Nesic, S.; Singer, M.
Highlights: A novel experimental setup was used to maintain the water chemistry of the electrolytes with well-defined mass transfer characterization. Ca 2+ incorporated into the crystal structure of FeCO3 and a substitutional iron-calcium carbonate solid solution was formed. The porous structure of Fe3 C networks provided "anchoring" sites for precipitation of FeCO3 enriched with calcium. The iron-calcium carbonate covered uniformly the steel surface and retarded the rate of the anodic reaction, causing lower general corrosion. Presence of Ca 2+ in the electrolyte, while bulk CaCO3 precipitation was not expected, did not lead to any localized corrosion. Abstract: The effect of Ca 2+ on the corrosion product layers when the CO2 -containing electrolyte is saturated with respect to CaCO3, as frequently observed in oil production systems, was studied by weight loss, electrochemical techniques, and surface characterizations. An improved experimental set up was used and all experimental parameters reported. Results show that precipitation of corrosion products in solutions with or without CaCO3 was due to the favorable water chemistry obtained at the steel surface compared to the bulk solution. The presence of Ca 2+ did not jeopardize the final protectiveness of corrosion product layer, but seemed to delay its growth.